Transformasi Pendidikan dan Kesadaran Sosial: Pengenalan Aplikasi Pembelajaran Berbasis Kecerdasan Buatan dan Kampanye Anti-Perundungan bagi Siswa SMP - Nafiah, Hana; Jumaroh, Jumaroh (Batik-MU : Jurnal Pengabdian Masyarakat, 2024)
This community service aimed to introduce alternative uses of technology to support English learning and raise awareness of bullying at SMP Muhammadiyah Pekajangan through two main programs: the introduction of artificial intelligence (AI)-powered learning applications and an anti-bullying campaign. AI applications such as Busuu, Mondly, Cake, ELSA Speak, and Loora were introduced as flexible, engaging, and affordable self-learning tools. Additionally, the anti-bullying campaign provided students with an understanding of the forms of bullying, its impacts, and ways to address it. The results showed positive responses from students toward both programs. It is recommended that the school supports the continued use of AI applications and regularly organizes similar activities to create a safer, more inclusive learning environment that fosters student development.